93KORELASI PEMAHAMAN KOSAKATA BIDANG PENDIDIKAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMKN 1 PAYAKUMBUH - Dewi, Triwina Santi; Tressyalina, Tressyalina; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACTÂ This article was written to see the correlation of vocabulary understanding of education with the skills of writing expositional text of grade X students of SMK Negeri 1 Payakumbuh. This research data in the form of score test result of vocabulary comprehension of field of education and score of skill of writing exposition text. The data is obtained through two types of tests, ie objective tests to measure the vocabulary understanding of the field of education and performance tests to measure the skills of writing expository texts. Based on the results of data analysis can be concluded that there is a significant correlation between the correlation of vocabulary understanding of education with the skills of writing expositional text of students of Class X SMK Negeri 1 Payakumbuh at 95% significant level with dk = n-1. Based on the t-test the hypothesis is accepted because t count> t table is 16.21> 1.67.Â Kata kunci: korelasi, kosakata, menulis, teks eksposisi